Immunological changes in patients with community-acquired pneumonia with concomitant coronary artery disease during treatment with Simvastatin - V. V. Syvolap; L. O. Kurilets; L. V. Lukashenko; A. O. Yarosh (Zaporožskij Medicinskij Žurnal)
(cellular and humoral immunity, mucosal immunity, the complement system, and so on). With features of immune system in the elderly people related some of clinical problems: hypersensitivity to non- and intra-hospital infections, subacute infection that increases concomitant diseases, especially cardiovascular.